Civic Identity and Piety in Platoʼs Laws - Bartninkas, Vilius (Literatūra, 2016)
This paper explores the meaning of religion and piety in Plato’s Laws. A discussion of contemporary scholarship shows that currently there is a trend to emphasize ethical innovations in Plato’s later thought without discussing its relation to religion. However, an analysis of the key foundational narratives of Magnesia reveals that religion has a substantial role in the dialogue. Plato rethinks the meaning of piety in his last dialogue. On the one hand, he criticizes the traditional Greek religiosity by providing a way to reconcile the performative and the rational devotion to gods. On the other hand, piety is incorporated in ethical theory as a key structural component. Thus, piety emerges as one of the most fundamental ideas in the political project of Magnesia.